The Effects of an Educational Program with Recitation of the Zikrullah on Fear, Pain and Duration of First Stage Labor Among Muslim Primiparous Women - Hitae, Nuraihan; Kritcharoen, Sureeporn; Chatchawet, Warangkana (Princess of Naradhiwas University Journal, 2023)
This quasi-experimental research aimed to examine the effect of educational program with recitation of the Zikrullah on fear, pain, and duration of first stage labor among primiparous Muslim women as in an experimental group with the women in a control group who have been taken care by using the traditional method. There were 60 primiparous Muslim women of first-stage-labor who obtained from purposely selected sampling and were receiving care service from an antenatal clinic and delivering unit at Bannangsata Hospital, Yala province. They were assigned into an experimental group (30 participants) who received the educational program with recitation of the Zikrullah, and a control group (30 participants) who received usual nursing care. The research instruments comprised of three parts, including (1) An integrated educational program with the recitation of the Zikrullah, (2) The recording form of the Zikrullah recitation while giving birth, and (3) The questionnaires regarding personal, pregnancy, and delivery information. The instruments were content validated by three experts and the data received were analyzed using frequency, percentage, mean, standard deviation, chi-square, independent t-test, and Mann-Whitney U test. The results revealed that: (1) The experimental group had a mean score of fear during the active phase and the transitional phase statistically significantly less than that of the control group (t = 8.17, p < .001; t = 7.91, p < .001) (2) The experimental group had a mean score of pain during the active phase and the transitional phase statistically significantly less than that of the control group (t = 3.08, p < .001; U = 304.50, Z = -2.21, p < .05) and (3) The experimental group had an average duration of the first stage labor shorter than that of the control group (t = .82, p > .05) but the difference was not statistically significant. The results showed that the educational program with recitation of the Zikrullah could help to reduce fear and labor pain in the first stage of labor in primiparous Muslims. Thus, the nurses should apply this intervention with them in order to lessen the complications that would occur during the waiting period before giving birth.